Comparing sustainable methods for synthesis of natural benzaldehyde from trans‐cinnamaldehyde: Experimental analysis. Issue 4 (26th August 2020) - Dung, Nguyen Trung; Ha, Cao Hong; Meyer, Xuan‐Mi; Meyer, Michel; Blanco, Jean‐Francois; Cognet, Patrick
Abstract: Natural benzaldehyde is an aromatic flavor compound. Compared to the chemical synthesis route, the natural benzaldehyde that is produced from natural source such as cassia oil is very expensive. To overcome the problem, many researchers have reported and proposed different processes such as ozonization process, near‐critical water hydrolysis process, toxic phase transfer, or surfactants catalytic process. This paper presents a comparison of three green chemical routes using aqueous systems: (H2 O/OH ‐ ), (H2 O/OH ‐ /H2 O2 ), (H2 O, cellulose‐based heterogeneous catalyst/OH ‐ ), applied to this transformation. First experimental results show remarkable conversion for the first and third systems. Best yields are obtained using the first simple route with, for example, a nearly 80 % conversion together with a 43 % selectivity.